2021
DOI: 10.1002/adma.202104265
|View full text |Cite
|
Sign up to set email alerts
|

Tunable 2D Group‐III Metal Alloys

Abstract: Chemically stable quantum-confined 2D metals are of interest in next-generation nanoscale quantum devices. Bottom-up design and synthesis of such metals could enable the creation of materials with tailored, on-demand, electronic and optical properties for applications that utilize tunable plasmonic coupling, optical non-linearity, epsilon-near-zero behavior, or wavelengthspecific light trapping. In this work, we demonstrate that the electronic, superconducting and optical properties of air-stable two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…15 This interband transition is sensitive to the choice of metal intercalant, typically exhibiting a 50 nm red shift for indium with respect to gallium (Figure S1). The 2-D alloy interband transition energy can be tuned by the metal composition, 25 and the absorption peak is located between the 2-D In and 2-D Ga peaks (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…15 This interband transition is sensitive to the choice of metal intercalant, typically exhibiting a 50 nm red shift for indium with respect to gallium (Figure S1). The 2-D alloy interband transition energy can be tuned by the metal composition, 25 and the absorption peak is located between the 2-D In and 2-D Ga peaks (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of increased structural disorder was also obtained from high-resolution scanning transmission electron microscopy (STEM) images of the alloy (Figure 7c,d). 25 Previous statistical analysis of HR-STEM images of 2-D In revealed that the first metal layer is aligned directly above the Si, and the second layer exhibits a strong preference to sit directly above the carbon atoms of the top SiC layer. 14 This preference for a particular registry of the metal atoms over the SiC results in the same metal lattice orientation persisting across an entire terrace.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In this technique, atoms intercalate at the interface of EG and silicon carbide (SiC) substrates, which facilitates large-area, environmentally airstable 2D nitrides, 2,3 2D oxides, 4,5 2D metals, 1,6 and 2D alloys. 7,8 This air stability provided by the graphene cap is the key ingredient for next-generation quantum, high-frequency electronics, optical, and sensing technologies. 9 In addition, the use of EG enables superior heterostructure quality compared to graphene transferred by liquid methods.…”
Section: Introductionmentioning
confidence: 99%